The impact of parasitic diseases on dromedary camel (Camelus dromedarius) welfare: a comprehensive review - Nawaz, Saqib; Tharwat, Mohamed (Frontiers in Veterinary Science, 2026)
The dromedary camel (Camelus dromedarius) is a multifunctional animal indispensable for the livelihoods and food security of pastoralist communities residing in arid and semi-arid regions. Despite its socio-economic and cultural significance, the welfare of camels has garnered limited scientific scrutiny, particularly regarding the effects of parasitic diseases. These diseases pose a significant barrier to camel health, resulting in considerable production losses and severe welfare challenges. This review consolidates evidence on the impact of parasitic infections, which include hemoparasites (Trypanosoma evansi, Babesia, and Theileria), ectoparasites (ticks and mange mites), and endoparasites (gastrointestinal nematodes and coccidia) on the welfare of dromedary camels. We investigate the physiological and emotional repercussions of parasitism through the lenses of the Five Freedoms and the Five Domains model. This review demonstrates that parasitic diseases severely impact camel welfare, yet it highlights significant deficiencies in the species-specific assessment and surveillance systems needed to address these problems. Furthermore, it underscores the relationship between camel welfare, human health through zoonotic parasites, and the socio-economic stability of pastoral communities. The review concludes that an integrated, multidisciplinary approach combining veterinary parasitology, animal welfare science, and socioeconomics is urgently required. We advocate for the implementation of a cohesive One Health/One Welfare framework to establish validated welfare indicators, enhance diagnostic and control strategies, promote community engagement, and inform effective policies. This strategy is crucial for alleviating suffering, improving productivity, and sustaining livelihoods that depend on camels in the face of climate change.